2022
DOI: 10.3390/molecules27196411
|View full text |Cite
|
Sign up to set email alerts
|

Elsholtzia ciliata (Thunb.) Hyland: A Review of Phytochemistry and Pharmacology

Abstract: In this paper, the confusion of the sources of medicinal materials was briefly expounded, and the differences among the varieties were pointed out. At the same time, the chemical components and pharmacological properties of Elsholtzia ciliata (Thunb.) Hyland (E.ciliata) were reviewed. The structures of 352 compounds that have been identified are listed. These mainly include flavonoids, terpenoids, phenylpropanoids, alkaloids, and other chemical components. They have antioxidant, anti-inflammatory, antimicrobia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In the crude extracts of E. ciliate (Thunb. ), more than 350 compounds have been identified, including monoterpenes, phenylpropanoids, flavonoids, and alkaloids ( Wang et al, 2022 ). ECO mainly consists of small-molecule compounds such as monoterpenes, sesquiterpenes, and diterpenes ( Chen S. et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the crude extracts of E. ciliate (Thunb. ), more than 350 compounds have been identified, including monoterpenes, phenylpropanoids, flavonoids, and alkaloids ( Wang et al, 2022 ). ECO mainly consists of small-molecule compounds such as monoterpenes, sesquiterpenes, and diterpenes ( Chen S. et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the practice of traditional Chinese medicine, it is commonly used for heatstroke, chest tightness, halitosis, acute gastroenteritis, etc. ( Hou and Jiang, 2013 ; Wang et al, 2022 ). E. ciliata contains many volatile essential oils to produce a strong aroma, of which the main components are terpenoids and phenolic compounds, with the highest content being monoterpenoids ( Pudziuvelyte et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elsholtzia ciliata is widely distributed throughout Korea, China, and Europe. In Poland, it grows mainly in the eastern regions [ 97 , 98 ]. An in vivo study found that ethanol extract from this plant inhibits renal interstitial fibrosis induced by unilateral ureteral obstruction.…”
Section: Plants Whose Therapeutic Effect On the Urinary Tract Has Bee...mentioning
confidence: 99%
“…R-carvone is the active ingredient in E. ciliate essent against Liposcelis bostrychophila. The LC50 of contact toxicity was 57.0 µg/cm 2 , a fumigant toxicity was 417.4 mg/L, respectively [23]. Thus, it is also necessary to i the insecticidal activity of compounds in the E. ciliata essential oil against L. serrico Some studies have shown that E. ciliata has an insecticidal effect [17].…”
Section: Introductionmentioning
confidence: 99%